Vertical fluxes of NO < inf> x , HONO, and HNO < inf> 3 above the snowpack at Summit, Greenland - Honrath, R. E.; Lu, Y.; Peterson, M. C.; Dibb, J. E.; Arsenault, M. A.; Cullen, N. J.; Steffen, K. (Atmospheric Environment, 2002)
Vertical gradients of NOx, HONO, and HNO3 were measured in the lower 1-2 m above the snowpack at Summit, Greenland, during summer 2000. These measurements are used with simultaneous measurements of atmospheric turbulence using eddy covariance systems to determine the vertical fluxes of NOx, HONO, and HNO3. Upward fluxes of NOx and HONO were observed; these emissions were highly correlated with diurnally varying sunlight intensity, consistent with the expectation that they are the result of nitrate photolysis within the snowpack. The HNO3 flux was smaller in magnitude and more variable than those of HONO and NOx. It was usually downward, but emission was occasionally observed during mid-day. The 24-h average NOx emission (2.52×1012 molecules m-2 s-1) and HONO emission (4.64×1011 molecules m-2 s-1) rates were not balanced by the average HNO3 deposition rate (7.16×1011 molecules m-2 s-1), indicating that NOx export may slowly remove nitrogen from the system composed of the atmospheric boundary layer plus the top few cm of the surface snowpack, potentially affecting the amount of nitrate ultimately stored in glacial ice. These measurements imply that snowpack (NOx+HONO) emissions may alter NOx and (through HONO photolysis) OH levels in remote, snow-covered regions, but are small relative to other NOx sources on the global scale. © 2002 Elsevier Science Ltd. All rights reserved.